Mastitis dengan Depresi Postpartum: Literature Review - Ahmaniyah, Ahmaniyah; Indriyani, Ratna; Hidayati, Niken Wahyu; Aulia, Aulia; Satriawati, Arisda Candra (Fakultas Ilmu Kesehatan, 2023)
Mastitis is an inflammatory condition that occurs in breastfeeding mothers in the first month postpartum. The incidence of mastitis is around 9-20% which is caused by a lack of frequency of breastfeeding, errors in breastfeeding and pressure on the breast tissue. In this study, we examined the relationship between mastitis and postpartum depression. reviewed from Google Scholar database and other related websites. With the keywords